Integrasi Filsafat Ilmu dan Etika dalam Pengembangan Model Analisis Sentimen Berbasis IndoBERT pada Wacana #IndonesiaEmas2045 - Romindo Romindo; Mahyuddin K. M. Nasution (Yayasan Literasi Sains Indonesia, 2026)
The philosophy of science positions scientific knowledge as the result of a systematic and logical thought process grounded in clear ontological, epistemological, and axiological foundations. In the context of computer science, the philosophical approach serves as an essential framework to ensure that the development of artificial intelligence-based models is not merely technical in nature but also founded on rational reasoning and ethical responsibility. This study integrates the paradigm of the philosophy of science with the development of an IndoBERT-based sentiment analysis model for social media comments under the hashtag #IndonesiaEmas2045. Through ontology, this research establishes digital social interactions as a legitimate object of scientific inquiry; through epistemology, it applies computational logic and machine learning–based scientific methods to interpret public opinion; and through axiology, it utilizes the analytical results to understand societal perceptions and support data-driven public policy. The model testing results demonstrate high performance with an accuracy of 96.5%, validating the coherence between a philosophical scientific approach and an empirical computational methodology. Therefore, this study not only contributes to the advancement of Indonesian-language sentiment analysis technology but also strengthens the scientific dimension of computer science within the framework of the philosophy of science.